(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
It is written about the life and work of the famous writer Maqsud Sheikhzadeh and the drama of Jalaluddin Manguberdi, and his love for the country is shown. Maqsud Sheikhzada illuminates his love for the country in the image of Jalaluddin and describes it very beautifully.